INVESTIGATING CLASSROOM INSTRUCTION IN GRAMMAR CLASS USING INDUCTIVE APPROACH - Faisal, Muhammad; Misdi, Misdi (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
This study investigated whether the implementation of inductive approach increases studentsâ achievement in teaching grammar at the seventh grade students of SMP N 16 Cirebon. Richards et al, 1985 in Chalipa 2013 often said that Inductive approach is learning in which learners are not taught rules directly, but are left to discover - or induce - rules from their experience of using the language; Ke (2008, p.1) stated that inductive approach helps students to rediscover their subconscious knowledge of English grammar and gives advantages such as makes the sentence well-formed and grammatical competence, actively involves students in their grammar learning process, and helps students to understand. This study employed quasi experimental design. The finding supported the research hypothesis that inductive approach is potential for studentsâ achievement in learning grammar, especially Inductive approach made classroom atmosphere actively, it seem when inductive approach was implemented in teaching and learning process, almost students have enthusiasm to answer the question Keywords: Inductive Approach, Teaching Grammar